Araa’u Syauqy Dhaif Wa Juhuudihi Fi Tajdiid Ta’liim al- an-Nahwi li Ghair an-Nathiqiina bi al-Arabiyyah - Setiadi, Fadlan Masykura; Nur Balqis (Al Intisyar: Jurnal Pendidikan Bahasa Arab, 2024)
This research aimed to explore the thought and efforts of Shauqi Dhaif in modernizing the teaching of Arabic grammar for non-Arabic speakers as presented in his book "TajdÃ®d al-Nahw". The findings reveal that Shauqi Dhaif proposes significant innovations, including the elimination of speculative and local grammatical analysis (i'rab takdiri and i'rab mahalli), and emphasizes practical utility by establishing detailed definitions and rules for various aspects of grammar. Furthermore, his efforts in restructuring grammar materials involve thorough discussions on word structure, verb conjugations, letter classifications, types of nouns, and more efficient sentence constructions. This approach aims to enhance non-Arabic students' understanding of Arabic grammar, facilitate the teaching and learning process more effectively, and provide a stronger foundation for practical application in everyday language use.